2003
DOI: 10.1142/s0192415x03001545
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from the Roots ofLindera strychifoliaInduces Apoptosis in Lung Cancer Cells and Prolongs Survival of Tumor-bearing Mice

Abstract: Lindera strychifolia, a scandent shrub Lauraceous medicinal plant, has been used in Chinese traditional medicine as a palliative and an anti-spasmodic. It also shows cytotoxic effects against several tumor cell lines and inhibits marcromolecule biosynthesis. This study investigated the anti-tumor effects of L. strychifolia extract against lung cancer cells using in vitro and in vivo models. Two human lung cancer cell lines A549 (adenocarcinoma) and SBC-3 (small cell carcinoma), and a non-tumor cell line 3T3-L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Increase oral bioavailability of anticancer agents [95] Lindera strychifolia Roots Extract Induces apoptosis A-549 and SBC-3 human lung cancer cell line [96] (Continued) Cell cycle arrest in G0/G1 phase as well as decrease of cells in S -phase Human colorectal adenocarcinoma. [134] plagued by lung, colon, rectum and prostrate cancer.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Increase oral bioavailability of anticancer agents [95] Lindera strychifolia Roots Extract Induces apoptosis A-549 and SBC-3 human lung cancer cell line [96] (Continued) Cell cycle arrest in G0/G1 phase as well as decrease of cells in S -phase Human colorectal adenocarcinoma. [134] plagued by lung, colon, rectum and prostrate cancer.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…1. Fujiwara and co-workers have studied the inhibitory effects of extracts of Lindera strychifolia, which can induce inhibition of cell growth in a dose-dependent manner in human lung cancer, and did not show any significant cytotoxicity [27]. Additionally, L. strychifolia extracts significantly inhibited tumor growth at a concentration of 5 mg/mL in a mouse model.…”
Section: Anti-lung Cancer Activitymentioning
confidence: 99%
“…The well-known Uyaku compounds mentioned above, and other sesquiterpenes such as isolinderalactone, neolinderalactone, lindestrenolide lindenone, linderazulene, chamazulene, laurolitsine, isogermafurene have been summarized in previous other studies [2][3][4][5]. Recent studies demonstrated that Uyaku extract has antiviral activity [21], an inhibitory effect on prolyl endopeptidase [22], and is associated with anticancer activity in lungs [23]. It has also a potentially protective effect against post-ischemic myocardial dysfunction [24], and diabetic nephropathy [25].…”
Section: Tel: +81-(86)-235-7491mentioning
confidence: 99%